La Educación Universitaria Para La Sostenibilidad Arquitectónica. Caso Ecuador - Pérez P., Marina (European Scientific Journal, ESJ, 2016)
Among the main features of the architect profile features a wide profile with values, knowledge and skills, which define in terms of social, economic and cultural context of the user, the project is sustainable, to materialize with minimum energy consumption. Since the basics of architecture are studied, sustainability and architecture constrict their relationship as a result of the stage of defining how the project will selecting the materials used in construction, a decision that determines the intervention architect in the environment, specifying the alternative that has the architect to meet customer needs-user and that will be the presence or absence of sustainability in architecture. Official initiatives to incorporate environmental education in higher education, argue that training is required in professions for the protection, rehabilitation and environmental management. In this area, beginning from a documentary perspective of official initiatives, is presented in an analytical way, the presence of sustainability in formal education in architecture later cases of academic studies of environmental content, conducted at the Faculty are analyzed Architecture and Urbanism of the University of Cuenca, with reference to the content of the syllabi of the construction area at the end of the conclusions guidelines for the enrichment of university education in order to train architects for sustainability are proposed.